PENGEMBANGAN PEMBANGKIT LISTRIK TENAGA HIBRIDA MENGGUNAKAN TURBIN ANGIN SUMBU VERTIKAL TIPE DOUBLE-STAGE SAVONIUS DAN PANEL SURYA - Shinta Wuriyandani; Cecep E Rustana; Hadi Nasbey (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The research development of hybrid power plant using vertical axis wind turbine type double-stage savonius and solar panels has been done. Wind turbine have 2 blades of each stage and 1 piece of solar panels type ESM50W with spesification Vmp 17.2V, Imp 2.91A and maximum power of 50 W. This study aims to determine the output power produced by the solar panels, wind turbines and hybrid systems of both. Then the laboratory scale testing and data retrieval voltage, electrical currents, wind speed, turbine speed, and light intensity. Results showed that the test of the hybrid system affects the output power generated is equal to 46.03 W. Hybrid system of vertical axis wind turbine type double-stage savonius and solar panels are optimizing the potential of wind and solar energy as power generation hybrid system. Keywords: hybrid system, double-stage savonius, solar panels, power output, and efficiency.